Cloud-based multitemporal shoreline change analysis using google earth engine and DSAS: A case study of Canggu Beach, Bali, Indonesia - I Dewa Ayu Meia Damayanthi; Ni Nyoman Pujianiki; Silvia Gabrina Tonyes (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2025)
Canggu Beach, Bali, is a multifunctional coastal area that faces environmental pressures due to erosion and rapid coastal development. This study analyzed shoreline changes during the period 2016-2024 using multitemporal Sentinel-2 satellite images processed through the Google Earth Engine (GEE) platform. Shoreline extraction was performed using NDWI index and Otsu threshold method, with sea level stability control based on HYCOM data. Shoreline change analysis was conducted using Digital Shoreline Analysis System (DSAS) on 247 transects with Net Shoreline Movement (NSM) and End Point Rate (EPR) approaches. Results showed a dominant trend of accretion (NSM +16.61 m; EPR +2.26 m/year), with localized erosion (NSM -8.8 m; EPR -1.2 m/year), identified around estuary and structured areas. Spatial patterns of change were visualized in the form of multitemporal maps and statistical histograms, revealing uneven shoreline dynamics. The integration of GEE and DSAS proved effective for large-scale shoreline monitoring, and the results can provide a basis for adaptive coastal management in dynamic, multi-functional coastal areas.